Engineering the Atom-Photon Interaction Controlling Fundamental Processes with Photons, Atoms and Solids - Predojević, Ana; Mitchell, Morgan W. (Nano-Optics and Nanophotonics, 2015)
This book provides a comprehensive view of the contemporary methods for quantum-light engineering. In particular, it addresses different technological branches and therefore allows the reader to quickly identify the best technology - application match. Non-classical light is a versatile tool, proven to be an intrinsic part of various quantum technologies. Its historical significance has made it the subject of many text books written both from theoretical and experimental point of view. This book takes another perspective by giving an insight to modern technologies used to generate and manipulate quantum light.